Estimation of G x E Interaction by AMMI Model in ‘Antenna Panel’ Genotypes of Rice [Oryza sativa L.] - Deepayan Roy; Amit Kumar Gaur; Indra Deo Pandey (Brazilian Archives of Biology and Technology, 2022)
Abstract G × E interaction is major cause of discrepancy in crop yield under different environments. International Rice Research Institute (IRRI) launched their fourth flagship project on Global Rice Array (GRA-IV) to identify climate resilient rice genotypes. The G x E interaction was studied in ‘Antenna Panel’ genotypes Of rice using AMMI model. The results indicated that main effects as well as interactive G x E effects were significant for most of the traits. Major portion of the G x E was contributed by the genotypes. AMMI model having two principle components axis was found as the best predictive model. On the basis of biplots and ASV score SAHEL 177 for days to 50% flowering, SADRI for plant height; FEDEARROZ 50 for panicle length; CT11891-2-2-7-M for number of grains panicle-1 and SAHEL 108 for grain yield were considered as most stable genotypes in all the consecutive three environments. Moreover Yield Stability Index (YSI) supported the results that SAHEL 108 is the most superior genotype for grain yield over all the three environments of testing. Findings from this study are expected to help breeders to select suitable genotype on the basis of its performance and stability over locations. which can provide a head start to the rice improvement programmes for Indo-gangetic Plains and Hilly Tarai regions of India.